The body of constitutional control as a subject of constitutionalizing criminal procedure legislation - Rakhmetulin, А.Д. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The increasing influence of constitutional ideas and principles on the system of legal regulation, including the regulation of pre-trial and judicial stages of criminal proceedings, has had a serious impact on the emergence and development of the concept and practice of constitutionalizing the legal system in modern states. The same trend has also affected the sphere of criminal proceedings, since, firstly, it is objectified by the need to improve the system of protecting human and civil rights and freedoms. Secondly, this trend is due to the fact that the subjects of criminal proceedings involved in the criminal process, on the one hand, are protected by the rights that are established in constitutional norms and regulations, on the other hand, these rights may be restricted in cases provided for by law. Determination of the balance in this matter is provided by law enforcement agencies in the process of law enforcement activities. At the same time, when situations arise when there are doubts about the constitutionality of the norms of criminal procedure legislation, the Constitutional Court of the Republic of Kazakhstan has the last word in the dispute about the right, which expands the boundaries of constitutional legality through the adoption of regulatory decisions. In this aspect, the article analyzes the activity of the Constitutional Court of the Republic of Kazakhstan as one of the main subjects of the constitutionalizing the norms of criminal proceedings. The author of the article examines the work of the constitutional control body through the content of its normative resolutions, which are an important source of constitutionalizing criminal procedure law.